RTA-pcychology beyond freud - "Nirmal, Kumar" (Bombay, 1981)
This book challenges the myths of modern psychology and in that it renders immeasurable help to the modern man, the foundations of whose soul have been ruthlessly shaken by Freud and his legacy. Nirmal Kumar provides a scientific alternative to the gloomy study of Freud and proves that the latter$1 (Bs study was an exaggeration as it was based on the psychology of a frightened and shell-shocked Europe.s
Keywords: Psycology